OS06.5.A Investigating safety and efficacy of TTFields prior and concomitant to radiotherapy in newly diagnosed glioblastoma - the PriCoTTF phase I/II trial. (5th September 2022) - Kebir, S; Lazaridis, L; Schmidt, T; Oster, C; Feldheim, J; Glas, M; Pierscianek, D; Proescholdt, M; Hau, P; Grosu, A; Krex, D; Scheffler, B; et al.
Abstract: Background: The EF-14 phase III trial demonstrated improved survival for patients with newly diagnosed glioblastoma (nGBM) when TTFields therapy was added to adjuvant temozolomide chemotherapy. TTFields at 200 kHz are applied to the tumor utilizing arrays on the patients' scalp. In preclinical studies, a synergistic inhibiting effect on glioblastoma cell proliferation was found for the combination of TTFields and radiotherapy. Based on these findings, we conduct the phase I/II PriCoTTF trial in adult nGBM patients to investigate the safety and efficacy of TTFields therapy initiated prior and concomitant to radiochemotherapy. Material and Methods: Per study protocol, TTFields therapy is initiated following surgery and completed wound healing. Continuing throughout radiochemotherapy and adjuvant chemotherapy, TTFields therapy is used for approximately 9 months in total with TTFields rechallenge allowed at recurrence. Radiotherapy is conducted with arrays applied on the patients' scalp. A total recruitment of 33 patients was sought, with 20 patients in arm A receiving normo-fractionated radiotherapy, and 13 elderly patients in arm B receiving hypo-fractionated radiotherapy. Safety and tolerance are the study's primary endpoint, analyzed by a selection of pre-specified treatment-limiting toxicities (TLTs). Results: A total of 33 patients have been enrolled. Patients' characteristics were mostly typical for glioblastoma, except for a rather low fraction of patients with gross total resection (GTR, 22.5%). The distribution of adverse events of common toxicity criteria (CTC) grade 3 or higher was comparable to that of established glioblastoma trials. Notably, skin toxicity of CTC grade 3 or higher was quite uncommon (n=2, 6%). As no patient developed TLTs, the study's primary endpoint was met. Median TTFields treatment duration was 8.4 months. Overall survival data was not mature enough (event rate 48%) to allow for a definite conclusion. Notably, on multivariable Cox regression, the number of days with TTFields adherence of more than 23 hours was independently associated with overall survival (HR 0.96, 95% confidence interval 0.93 - 0.99, p=0.008). Conclusion: The PriCoTTF trial met its primary endpoint indicating that combined TTFields and radiotherapy is safe and well tolerated. High-grade skin toxicity was quite uncommon and the patients with high TTFields adherence seem to perform particularly well. An extended follow-up is required to provide first estimates regarding putative efficacy. At that point in time, the reduced overall TTFields duration and fraction of patients with GTR need to be factored in.